VALUES OF AKHLAQ EDUCATION IN TARBIYAH HIGH SCHOOLS (STIT) AL HIKMAH TEBING TINGGI - Ficki Pardede (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2021)
This article analyzes the values of moral education which are implemented at STIT Al Hikmah Tebing Tinggi. This study uses a qualitative research method with the fonomena approach. Based on a review of the explanation of the article, it is found that the results of the study show that the values of moral education implemented in STIT Al Hikmah Tebing Tinggi are included in spiritual values, honest values in academic ethics and the value of tolerance for pluralism. These three values are the integrated moral education category in learning and academic services at STIT Al Hikmah Tebing Tinggi. The goal in fostering the values of moral education at STIT Al Hikmah Tebing Tinggi is to build a sense of kinship by hoping for the pleasure of Allah SWT. So that in doing work both obligations and helping others in the frame of diversity